The Political Economy of Natural Resources: Exploitation and Sustainability - Loso Judijanto; Reza Ronaldo; Edy Setiawan (PT. Anagata Sembagi Education, 2024)
This article explores the political economy dynamics of natural resources in relation to their exploitation and sustainability. Natural resources, such as oil, gas, minerals, and forests, play a critical role in economic development. However, their management is often hindered by power imbalances, neoliberal policies, and pressures from globalization. Using a descriptive qualitative approach, the study analyzes how policies, economic structures, and political dynamics shape the exploitation of natural resources and their effects on social, economic, and environmental sustainability. The article emphasizes the need for sustainable development as a solution, focusing on integrating environmental sustainability, social inclusiveness, and equitable economic growth. By addressing these interconnected factors, the article argues that it is possible to achieve a balance between economic growth and the preservation of natural resources. Furthermore, it offers strategic recommendations for overcoming the challenges of exploitation and inequality in resource management. These recommendations include creating policies that prioritize fairness, transparency, and long-term sustainability. The article stresses the importance of inclusive and future-oriented governance, which ensures that natural resource wealth benefits all sectors of society, while minimizing environmental degradation. Such governance approaches can lead to more equitable outcomes, fostering a sustainable relationship between human development and the natural environment.